2021
DOI: 10.21834/ebpj.v6i17.2866
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Management Accounting System and Value Creation: An institutional perspective

Abstract: The emergence of environmental issues has increased environmental protection awareness among society and pushed organizations to become environmentally responsible. Many companies currently consolidate environmental matters into their corporate strategic plan by adopting a comprehensive Environmental Management Accounting System (EMAS) to create more value. However, a lack of understanding on the institutional pressures persuading EMAS adoption within the organizations has reduced the urgency for the company t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Proper identification and collection of physical and financial data enhances decisional process within the BUPT company and environmental data are no exception. Environmental accounting brings more information to management by identifying and quantifying measures such as (Yusoh et al, 2021):…”
Section: A Debate On Environmental Management Accounting Implementationmentioning
confidence: 99%
“…Proper identification and collection of physical and financial data enhances decisional process within the BUPT company and environmental data are no exception. Environmental accounting brings more information to management by identifying and quantifying measures such as (Yusoh et al, 2021):…”
Section: A Debate On Environmental Management Accounting Implementationmentioning
confidence: 99%
“…Several studies have identified different factors that could impact ESG implementation, such as internal factors, like organizational culture, leadership, and resources; and external factors, like market pressure, regulatory requirements, and stakeholder pressure. Mat Yusoh et al (2021) found that the most significant factors influencing ESG adoption among SMEs in Malaysia were internal factors, such as awareness, leadership support, and organizational culture. They also found that external factors, such as regulatory requirements and market pressure, had a moderate impact on ESG adoption among SMEs.…”
Section: Factors Of Sustainability Implementation Among Small and Med...mentioning
confidence: 99%
“…Proper identification and collection of physical and financial data enhances decisional process within the company and environmental data are no exception. Environmental accounting brings more information to management by identifying and quantifying measures such as [13]:…”
Section: Implementation Of Emamentioning
confidence: 99%